Convention on the simplification of formalities in trade in goods, Interlaken, 20 May 1987 : Council Decision on the position to be taken on behalf of the European Union within the EU-CTC Joint Committee established by the Convention of 20 May 1987 on the simplification of formalities in trade in goods and within the EU-CTC Joint Committee established by the Convention of 20 May 1987 on a common transit procedure, as regards an invitation to the United Kingdom to accede to those Conventions, Brussels, 25 September 2018 /: Council Decision on the position to be taken on behalf of the European Union within the EU-CTC Joint Committee established by the Convention of 20 May 1987 on the simplification of formalities in trade in goods and within the EU-CTC Joint Committee established by the Convention of 20 May 1987 on a common transit procedure, as regards an invitation to the United Kingdom to accede to those Conventions, Brussels, 25 September 2018. ([2018-12-05]) - Unknown
No abstract available